Gender lessons : girls and boys negotiating learning community in Basics of Music - Kuoppamäki, Anna ([A. Kuoppamäki], 2015)
This study examines the complexity of children's gendered negotiations in a music classroom, particularly how the age-related social phenomenon of gendered border work, gendered learner identities and the construction of musical agency are intertwined in these negotiations when learning music in a group. This study views 9-year-old children participating in a classroom discourse of the Finnish Music School Basics of Music (BoM) course, and aims to identify and analyze practices in which agency is either supported or restricted. Hence, it discusses both the complications and even the inequalities that children's gendered interaction may cause in learning, as well as situations in which social boundaries are crossed and multi-voicedness promoted. This study adopts a socio-cultural view of learning, taking a standpoint on gender that is socially constructed, performative and fluid. Further, it understands discourse extensively, that is, including also the artefacts, experiences and practices shared by the local community of learners, and seeks to discuss identity, agency and gender as lived relations that all are negotiated in social interaction with others. While considering the music classroom as a social space, in which identities and agencies are negotiated in the classroom discourse, this study argues that gendered border work interferes with students' learning processes when they negotiate memberships in a community of learners, and construct ownership of meaning and agency in music-making. This study is an ethnographic practitioner inquiry that experiments with different pedagogical solutions, and was therefore carried out in two types of settings: a co-ed setting and single-gender settings. The same children participated in both settings. This two-prong approach was important in order to understand how gendered border work is intertwined with the processes in which identities and agencies are negotiated collectively as well as individually. The data, collected during one semester (16 weeks) consists of: videotaped lessons; children's stimulated recall-interviews conducted in groups, individually and in pairs; and a teacher's research diary. The analysis uses multi-methodological lenses, including both concept-driven and data-driven qualitative analysis. Furthermore, in order to attend to the voices of the children participating in BoM, and to give the reader a taste of the ambiances and feelings and what gendered border work may be about, a narrative approach was used by presenting characters of 'Emma' and 'Amos'. These two narratives are representative constructions based on the experiences of several children who participated in the BoM classroom activities and, later, in the stimulated recall-interview sessions. The findings of this study suggest that, in the music classroom, for this particular age-group, children's gendered negotiations may create boundary issues, and thus, obstacles for democratic and meaningful learning to take place. In order to promote equal opportunities and collaborative learning, social issues, such as gender, need to be identified and treated openly and sensitively in the classroom discourse. In the BoM classroom under study, gendered border work took place in three ways: in adopting gender based learner identities; in holding gendered beliefs and pre- conceptions; and in falling into polarized 'good student' and 'rebel student' identities, thus driving the processes of negotiating memberships and constructing ownership of meaning. The study points out how, in particular, the use of student voice operates as a legitimator, regulating access to participation and contributing to shared meaning making. However, the findings suggest that, in a co-ed setting, the practices that support reflexivity and the processes of negotiating individual meanings de-emphasize gendered groupings among the children. In the BoM classroom, these practices involve individual creative activities, such as the students inventing own rhythmic patterns or compositions, which allowed them to draw from their own personal worlds. In these situations, the students were able to cross the gender boundaries and engage in learning collaboratively.

Tutkimuksessa tarkastellaan, kuinka lasten sukupuoleen sidottu rajatyön käsite (gendered border work), oppijaidentiteetit ja musiikillinen toimijuus kietoutuvat toisiinsa musiikin ryhmäoppimisessa. Tutkimuksessa analysoidaan yhdeksänvuotiaiden lasten osallistumista luokkahuonediskurssiin musiikkiopiston "Musiikin perusteiden" tunneilla. Tutkimus pohjautuu sosiokulttuuriseen oppimiskäsitykseen. Sukupuoli (gender) ymmärretään sosiaalisesti rakentuneena, performatiivisena ja prosessimaisena. Identiteettiä, toimijuutta ja sukupuolta tarkastellaan alati muuttuvina sosiaalisina suhteina, joista neuvotellaan vuorovaikutuksessa toisten kanssa. Musiikkiluokka nähdään siis sosiaalisena tilana, jossa identiteeteistä ja toimijuuksista neuvotellaan luokkahuonediskurssissa. Diskurssi ymmärretään laajassa merkityksessä sisältämään myös oppijoiden keskenään jakamat artefaktit, kokemukset ja käytännöt. Aineiston kautta tarkastellaan lasten sukupuolineuvottelusta mahdollisesti aiheutuvia oppimisen vaikeuksia tai jopa eriarvoisuutta aiheuttavia tekijöitä, mutta myös tilanteita joissa sosiaalisia raja-aitoja ylitetään ja moniäänisyyttä tuetaan. Tutkimuksen perusteella esitetään, että lasten sukupuolinen rajatyö vaikuttaa oppilaiden oppimisprosseihin erilaisissa musiikin tekemisen tilanteissa ryhmäjäsenyyksistä, merkityksistä, omistajuudesta ja toimijuudesta neuvoteltaessa. Tutkimus on etnografinen practitioner inquiry, jossa tutkija toimii sekä opettajana että tutkijana kokeillen erilaisia oppimisyhteisön ideaalia tavoittelevia pedagogisia ratkaisuja. Tämän vuoksi tutkimus on toteutettu kahdessa vaiheessa: sekaryhmässä sekä tyttöjen ja poikien erillisissä ryhmissä. Tutkimuksessa samat lapset osallistuvat molempiin vaiheisiin. Kaksivaiheisuus mahdollistaa erityisesti sen tarkastelemisen, kuinka sukupuolinen rajatyö kietoutuu prosesseihin, joissa identiteeteistä ja toimijuuksista neuvotellaan sekä yhteisön että yksilön tasolla. Aineisto on kerätty yhden lukukauden (16 viikkoa) aikana, ja se koostuu videoiduista oppitunneista, ryhmä-, yksilö- ja parihaastatteluina toteutetuista lasten stimulated recall -haastatteluista sekä opettajan tutkimuspäiväkirjoista. Analyysissä on hyödynnetty sekä käsite- että aineistolähtöistä laadullista sisällönanalyysiä ja narratiivisia menetelmiä. Narratiivista lähestymistapaa on käytetty koostettaessa useamman lapsen kertomuksista hahmot "Emma" ja "Amos", jotka ovat representatiivisia konstruktioita (representative construction) luokkahuoneen aktiviteetteihin ja stimulated recall - haastatteluihin osallistuneiden lasten kokemuksista. Hahmojen tarkoituksena on nostaa esiin tutkimukseen osallistuneiden lasten ääni ja valottaa lukijalle tutkimuksen kohteena olleen luokan tunnelmia ja tunteita sekä lasten sukupuolisen rajatyön mahdollisia piirteitä. Tutkimuksessa osoitetaan, kuinka musiikkiluokassa ja tutkimuksen kohteena olevassa ikäryhmässä lasten sukupuolineuvotteluissa saattaa rakentua sosiaalisia raja-aitoja, jotka haittaavat demokraattisen ja mielekkään oppimisen toteutumista. Yhdenvertaisten mahdollisuuksien ja yhteistyössä tapahtuvan oppimisen tukeminen edellyttää sosiaalisten tekijöiden, kuten sukupuoleen liittyvien neuvottelujen, tunnistamista ja sensitiivistä käsittelyä luokkahuonediskurssissa. Tutkimuksen kohteena olleessa musiikin perusteiden opetusryhmässä lasten sukupuolinen rajatyö ilmeni kolmella tavalla ohjaten prosesseja, joissa ryhmäjäsenyyksistä ja oppimisen merkityksistä neuvoteltiin lasten kesken: (1) sukupuoleen sidotun oppijaidentiteetin omaksumisena, (2) sukupuoleen sidottujen käsitysten ja ennakkoluulojen ylläpitämisenä ja (3) polarisoituneiden ns. "kiltin oppijan" ja "villin oppijan" identiteettien ylläpitämisenä. Erityisesti sukupuolittuneet erot oppilaiden puheessa vaikuttivat oppilaiden mahdollisuuksiin osallistua ja vaikuttaa yhteisistä merkityksistä neuvotteluun. Tutkimus osoittaa kuitenkin, että ns. sekaryhmässä käytännöt, jotka tukivat refleksiivistä oppimista ja yksilöllistä merkityksistä neuvottelua vähensivät sukupuolittuneita ryhmäjakoja lasten keskuudessa. Tällaisia olivat käytännöt, jotka sisälsivät myös yksilöllisiä ja omasta elämysmaailmasta ammentavia luovia prosesseja, kuten oppilaiden omien rytmisten ostinatojen keksimistä tai säveltämistä. Näissä luokkatilanteissa oppilaat saattoivat ylittää sukupuoleen sidottuja raja-aitoja ja osallistua oppimiseen yhteistyössä toisten kanssa.
Keywords: musiikkikasvatus; sukupuoli; identiteetti; toimijuus; yhteisöllinen oppiminen; musiikkioppilaitokset; musiikki; perusopetus; fi=musiikkikasvatus|sv=musikpedagogik|en=Music Education|